Towards a molecular classification of colorectal cancer - Alessandro Lugli (Frontiers Research Topics, 2015)
In 2007, Jeremy Jass proposed a molecular classification of colorectal cancer including KRAS, BRAF, Mismatch Repair, CIMP and MGMT Status. Since then, many prognostic and predictive studies have been published on this topic, mainly focusing on one single molecular marker. The aim of the e-book is to summarize the knowledge in 2014 from a multidisciplinary point of view that can potentially be used as a manual by CRC researchers in every field.